Transvaginal Ultrasound Findings Among the Women Presenting with Infertility - Hussain, Nafeesa Binti; Das, Rinku Rani (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Introduction: Infertility is a difficult conditions for the obstetricians to dealwith. Transvaginal ultrasound (TVS) is a investigation that is primarily done to evaluate the cases of infertility cases. The objective of the present study was to document the Transvaginal Scan (TVS) findings in women presenting with infertility in a teaching hospital of Bangladesh. Methods: Subjects were women of reproductive age presenting at the teaching hospital with infertility over a one year period. As part of their management, transvaginal scans was done. TVS was done by the researcher herself and was checked by a second observer. Data was complied and analyzed by SPSS 20. Results: Among the 100 cases regarding anthropometric variables where mean ± SD of age was found 28 ± 6.7 years, weight was 56 ± 12.5 kg, height 1.57 ± 0.76 m and BMI was 24.5 ± 3.6 Kg/m2. Type of infertility revealed 75% cases were primarily infertile and 25% having secondary infertility. Comorbid diseases revealed 6% cases had DM, 4% cases had HTN, 11% cases had PID, 14% patients had thyroid problems. All the 100 cases undergone TVS study where PCO was found among 69(69%) cases, chronic pelvic inflammatory disease 14(14%) fibroids 6(6%) anatomical problems 19(19%) endometrial/cervical polyp 18(18%) free fluid in pelvic/abdominal cavity 7(7%) endometritis 5(5%) endometriosis 4(4%) adenomyosis 5(5%) chocolate cyst 8(8%) tubo-ovarian mass 2(2%) intrauterine and intra pelvic adhesions 2(2%) septate uterus 292%) pelvic abscess 1(1%) and ectopic pregnancy 1(1%). Conclusions: Polycystic Ovaries (PCO) is the major finding in women with infertility in our study. This hitherto poorly recorded pathology should be actively investigated in women representing with these symptoms by the use of TVS. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 31-34